Parametric analysis on hybrid ocean thermal energy conversion system - Yasuyuki IKEGAMI; Takeshi YASUNAGA; Natsuki KOYAMA; Tomoya OKUNO (Nihon Kikai Gakkai ronbunshu, 2020)
The hybrid ocean thermal energy conversion (OTEC) cycle is a combined system of a desalination and an OTEC, which generates power using the temperature difference between the surface and depth in the ocean. The system will produce the electric power and the distilled water from seawater, simultaneously. This cycle uses low pressure steam as warm heat source generated by a flash evaporation in vacuumed condition instead of flowing the surface seawater. This method has advantages: to prevent the performance degradation of the evaporator caused by the fouling due to marine organisms, to improve the heat transfer, and to allow to use the stainless steels instead of the titanium for an evaporator of OTEC for cost reduction. In this study, the parameter analysis was conducted to examine the effect of the working fluid flow rate and the evaporator heat transfer performance on the net power generation, water production ratio, and exergy efficiency based on concept of the finite-time thermodynamics. As the results, the evaporator heat transfer performance increases the power output, the exergy efficiency, and the maximum performance in each condition are increased, respectively. Notably, the maximum net power output is proportional to square of difference between a root of warm seawater temperature and a root of cold seawater temperature, whereas the water production ratio is proportional to temperature difference between a warm and a cold heat source temperatures.